Platelet signaling at the nexus of innate immunity and rheumatoid arthritis - Jiang, Steven Z.; To, Jeffrey L.; Hughes, Michael R.; McNagny, Kelly M.; Kim, Hugh (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a debilitating autoimmune disorder characterized by chronic inflammation of the synovial tissues and progressive destruction of bone and cartilage. The inflammatory response and subsequent tissue degradation are orchestrated by complex signaling networks between immune cells and their products in the blood, vascular endothelia and the connective tissue cells residing in the joints. Platelets are recognized as immune-competent cells with an important role in chronic inflammatory diseases such as RA. Here we review the specific aspects of platelet function relevant to arthritic disease, including current knowledge of the molecular crosstalk between platelets and other innate immune cells that modulate RA pathogenesis.